Study on the construction of multi-level protection system for non-emergency transfer under the perspective of structuring - Wei Liu; Ruiqiang Chen (Frontiers in Public Health)
IntroductionThe non-emergency transfer multi-level protection system is a pivotal livelihood endeavor in China, serving as a vital diversified component within the robust framework of a Chinese-style modern social security system. This system faces various challenges, including displacement of emergency capacity by non-emergency demands, uneven allocation of transfer resources, service quality variations, inadequate management structures, limited regulatory frameworks, and social acceptance issues.MethodsLeveraging structural theory, this study analyzes the primary issues in the current implementation of China’s non-emergency transfer security system. A structured approach is employed to investigate these challenges and propose solutions.ResultsThe study identifies key areas for improvement in the non-emergency transfer security system. It highlights the need for an enhanced internal resource allocation mechanism to boost service efficiency, skilled workforce development to improve service quality, optimized management systems and coordination mechanisms to strengthen patient confidence in recovery, and strengthened comprehensive information technology management for market oversight.DiscussionThe proposed structured approach aims to foster sustainable development of the non-emergency transfer security system within a positive feedback loop. The recommendations aim to address the identified challenges and enhance the overall effectiveness of the system. By improving resource allocation, workforce skills, management systems, and information technology, the study suggests fostering deeper emotional engagement and connections, ultimately contributing to the system’s long-term success.